1967
DOI: 10.1042/bj1040095
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-catalysed conjugations of glutathione with unsaturated compounds

Abstract: 1. Rat-liver supernatant catalyses the reaction of diethyl maleate with glutathione. 2. Evidence is presented that the enzyme involved is different from the known glutathione-conjugating enzymes, glutathione S-alkyltransferase, S-aryltransferase and S-epoxidetransferase. 3. Rat-liver supernatant catalyses the reaction of a number of other alphabeta-unsaturated compounds, including aldehydes, ketones, lactones, nitriles and nitro compounds, with glutathione: separate enzymes may be responsible for these reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(134 citation statements)
references
References 17 publications
4
129
1
Order By: Relevance
“…Diethylmaleate (DEM) is an indirect oxidant that yields an accumulation of endogenously produced ROS through a GSH depletion (20 and DEM induce ERKs activation. Cell lysates containing 25 g of proteins were resolved by electrophoresis on a 10% SDS-PAGE, transferred to a nitrocellulose membrane, and subjected to immunoblot analysis with antibodies specific for phospho-ERKs.…”
Section: Effects Of Redox Changes Mediated By Dem and H 2 O 2 -mentioning
confidence: 99%
See 1 more Smart Citation
“…Diethylmaleate (DEM) is an indirect oxidant that yields an accumulation of endogenously produced ROS through a GSH depletion (20 and DEM induce ERKs activation. Cell lysates containing 25 g of proteins were resolved by electrophoresis on a 10% SDS-PAGE, transferred to a nitrocellulose membrane, and subjected to immunoblot analysis with antibodies specific for phospho-ERKs.…”
Section: Effects Of Redox Changes Mediated By Dem and H 2 O 2 -mentioning
confidence: 99%
“…We previously developed a procedure to induce redox modification in intact cells (19): this is based on the exposure of cells to diethylmaleate (DEM), a GSH depleting agent (20). This experimental system allows the alteration of the concentrations of endogenously generated ROS by inactivating the scavenging systems based on GSH, through the formation of GSH-DEM conjugates.…”
mentioning
confidence: 99%
“…That GSH might be involved in the lectin-activated proliferation of T lymphocytes (T cells) was suggested by studies in which human peripheral blood lymphocytes were found to exhibit decreased proliferation after treatment with diamide (5) and with 2-cyclohexene-1-one (6). Diamide decreases GSH levels by oxidizing GSH (7), and compounds such as 2-cyclohexene-1-one react with GSH to form conjugates (8); however, these compounds act nonspecifically and thus may be expected to have effects other than depletion of GSH. Studies in this laboratory (4,9) and subsequently in others (10)(11)(12)(13) in which peripheral blood mononuclear cells were treated with L-buthionine-(S,R)-sulfoximine (BSO) (14)(15)(16), which selectively inhibits y-glutamylcysteine synthetase and thus GSH synthesis, gave much stronger support to the view that GSH is required for proliferation.…”
mentioning
confidence: 99%
“…27) In addition, enzyme-catalyzed alkylation of the thiol group of cystein with a,b-unsaturated carbonyl compounds has been observed. 28) The antimicrobial activity of a,b-unsaturated ketones is due to their reactions with essential thiol groups in bacteria and fungi, resulting in b-ketothioethers. 29) Electron densities on b-carbons are lower 30) than on a-carbons in various unsaturated ketones, and thus the attack of the nucleophils should occur at the b-carbon atoms.…”
mentioning
confidence: 99%